2019
DOI: 10.1111/cns.13101
|View full text |Cite
|
Sign up to set email alerts
|

Propofol improved hypoxia‐impaired integrity of blood‐brain barrier via modulating the expression and phosphorylation of zonula occludens‐1

Abstract: Summary Aims Hypoxia may damage blood‐brain barrier (BBB). The neuroprotective effect of propofol has been reported. We aimed to identify whether and how propofol improved hypoxia‐induced impairment of BBB integrity. Methods Mouse brain microvascular endothelial cells (MBMECs) and astrocytes were cocultured to establish in vitro BBB model. The effects of hypoxia and propofol on BBB integrity were examined. Further, zonula occludens‐1 (ZO‐1) expression and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…In addition, the supplementary data showed that propofol had no effect on TNF-α-modulated ZO-1 expression. Although it has been reported that propofol attenuated hypoxia-modulated ZO-1 expression in mouse brain microvascular endothelial cells [27,32]. We reasoned that hypoxia and inflammation may reduce ZO-1 expression through different intracellular signaling pathway, and that propofol may have different effect on these pathways.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the supplementary data showed that propofol had no effect on TNF-α-modulated ZO-1 expression. Although it has been reported that propofol attenuated hypoxia-modulated ZO-1 expression in mouse brain microvascular endothelial cells [27,32]. We reasoned that hypoxia and inflammation may reduce ZO-1 expression through different intracellular signaling pathway, and that propofol may have different effect on these pathways.…”
Section: Discussionmentioning
confidence: 93%
“…41 Previous studies of BBB permeability in CSVD have focused on tight junction proteins, such as zonula occludens-1 (ZO-1), occludin, and claudin-5. 42,43 The decreased expression of claudin-5, the key tight junction protein of the BBB, has been reported in a CSVD model. 38 In addition, growing evidence has indicated that limited caveolae-mediated transcytosis maintains BBB integrity in the CNS, 44 and BBB disruption due to increased vesicle transport has been confirmed in many models.…”
Section: Discussionmentioning
confidence: 89%
“…The impairment of the BBB predicts cognitive impairment at one year . Previous studies of BBB permeability in CSVD have focused on tight junction proteins, such as zonula occludens‐1 (ZO‐1), occludin, and claudin‐5 . The decreased expression of claudin‐5, the key tight junction protein of the BBB, has been reported in a CSVD model .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the supplementary data showed that propofol had no effect on TNF-αmodulated ZO-1 expression. Although it has been reported that propofol could attenuate hypoxiamodulated ZO-1 expression in mouse brain microvascular endothelial cells [ 27,32]. We reasoned that hypoxia and inflammation may reduce ZO-1 expression through different intracellular signaling pathway, and that propofol may have different effect on these pathways.…”
Section: Discussionmentioning
confidence: 93%